Social responsibility, technology and AI - Crowther, David; Seifi, Shahla (Developments in corporate governance and responsibility, 2024)
Artificial Intelligence (AI) has become one of the most talked about innovations of the present. There seems to be a general assumption that AI and technology of various forms can be used to achieve sustainability, but there is less discussion about how this can happen and whether there are both positives and negatives to technology and its use. This edited collection builds on the ethical questions reminiscent of those raised by early fiction writing in relation to robotics, and AI's position within human endeavour. The chapters recognise the dangers as well as the applications which are appropriate and helpful. Developments in Corporate Governance and Responsibility offers the latest research on topical issues by international experts and has practical relevance to business managers.